Association of sepsis severity with serum ferritin in the pediatric intensive care unit - Susanto, Yohanes; Wati, Dyah Kanya; Artana, I Wayan Dharma; Wati, Ketut Dewi Kumara; Widnyana, Anak Agung Ngurah Ketut Putra; Adnyana, I Gusti Agung Ngurah Sugitha (Indonesian Pediatric Society, 2025)
Background Sepsis remains a leading cause of pediatric intensive care unit (PICU) admissions in Indonesia. Serum ferritin is a potential biomarker for sepsis severity that requires validation. Objective To evaluate the association between serum ferritin and sepsis severity in children. Methods In this cross-sectional study, we consecutively enrolled children with sepsis (aged 1 month to 18 years) with lactate-excluded PELOD-2 scores of ≥7 admitted to the PICU of a tertiary referral hospital. Severe sepsis was defined as a PELOD-2 score of ≥11. Serum ferritin levels were measured at the time of PELOD-2 assessment. We determined the optimal ferritin cut-off point for severe sepsis by ROC analysis and performed bivariate and multivariate analyses to assess the association of ferritin level with sepsis severity. Results Among 74 subjects, 48.6% had severe sepsis. Serum ferritin concentration showed excellent discriminative power for severe vs. non-severe sepsis, with an area under curve (AUC) of 80% (95%CI 69.7-90.4%; P<0.001). The optimal serum ferritin cut-off level was 1,473.88 ng/mL, with a sensitivity of 80.6% and specificity of 78.9%. Severe sepsis was strongly correlated with elevated ferritin [bivariate prevalence ratio (PR) 3.8 (95%CI 2.0 to 8.2; P<0.001); adjusted PR 3.9 (95%CI 1.7 to 8.6; P=0.001)]. Conclusion Serum ferritin may serve as a biomarker for severe sepsis in children with good discriminative performance and may be useful for risk stratification of pediatric sepsis.